Examining rural-urban disparities in perceived need for health care services among adults with disabilities - Gimm, Gilbert; Ipsen, Catherine (Frontiers in Rehabilitation Sciences, 2022)
Purpose: The purpose of this study is to parse out differences between unmet need and perceived need for health care services among rural and urban adults with disabilities in the United States. While unmet need focuses primarily on environmental factors such as access to health insurance or provider availability, perceived need relates to personal choice. This distinction between unmet and perceived need is largely ignored in prior studies, but relevant to public health strategies to improve access and uptake of preventive care. Methods: Using Wave 2 data from the National Survey on Health and Disability, we explored rural and urban differences in unmet and perceived health care needs among working-age adults with disabilities for acute and preventive services. Findings: Although we found no significant differences in unmet needs between rural and urban respondents, we found that perceived needs for dental care and mental health counseling varied significantly across geography. Using logistic regression analysis and controlling for observable participant characteristics, we found that respondents living in noncore counties relative to metropolitan counties were more likely to report not needing dental care (OR 1.89, p =.028), and not needing mental health counseling services (OR 2.15, p ≤ .001). Conclusion: These findings suggest additional study is warranted to understand perceived need for preventive services and the levers for addressing rural disparities.